2022
DOI: 10.1001/jamanetworkopen.2022.17380
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Activity and Healthy Eating Behaviors Among US Adults Receiving Bariatric Surgery

Abstract: Key Points Question What are the differences in lifestyle patterns among individuals who received bariatric surgery compared with those eligible for surgery who did not receive it and those with normal weight? Findings In this cross-sectional study of 4659 participants, postbariatric surgery patients reported more time spent on physical activity (50.6 min/wk) and lower total energy intake (−295 kcal/d) than those eligible for surgery, with levels of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…32 Similarly, assessments of PA among US adults with normal weight and those eligible for (Class 3 obesity) and receiving bariatric surgery showed that compared to those with normal weight, those eligible (with Class 3 obesity) were significantly more likely to report lower physical functioning (i.e., mobility), and less PA (111.9 min/wk). 33 If our findings are representative of other Southern AAW living in rural settings, they have important implications for how we approach behavioral lifestyle weight loss interventions targeting this group of women. In the paragraphs below we discuss our findings in the context of existing weight loss intervention research and describe implications for future intervention research to address the PA needs of Southern AAW living with severe obesity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…32 Similarly, assessments of PA among US adults with normal weight and those eligible for (Class 3 obesity) and receiving bariatric surgery showed that compared to those with normal weight, those eligible (with Class 3 obesity) were significantly more likely to report lower physical functioning (i.e., mobility), and less PA (111.9 min/wk). 33 If our findings are representative of other Southern AAW living in rural settings, they have important implications for how we approach behavioral lifestyle weight loss interventions targeting this group of women. In the paragraphs below we discuss our findings in the context of existing weight loss intervention research and describe implications for future intervention research to address the PA needs of Southern AAW living with severe obesity.…”
Section: Discussionmentioning
confidence: 90%
“…Healthy Eating Index scores have been shown to be significantly lower for those with Class 3 obesity compared to those with normal weight. 33 We posit that a possible driver of the lack of dietary differentiation seen above BMI > 25 in this rural population may be related to social support. In a small study of 195 rural AAW with overweight and obesity living in the Deep South of the US, women reported minimal receipt of social support from family and friends for healthy eating or exercise behaviors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…9,[20][21][22] Overall, poor diet quality is commonly reported in this population. 9,20,[22][23][24][25] Two studies showed that diet quality of individuals who had previously undergone bariatric surgery was lower compared to individuals with normal weight. 23,25 This highlights the importance of improving dietary habits in the first month following surgery and not solely relying on the initial benefits of the bariatric procedure.…”
Section: Discussionmentioning
confidence: 99%
“…9,20,21 However, this goal appears to be difficult to achieve because poor diet quality is frequently reported in this population. 9,20,[22][23][24][25] Although most studies generally report a low consumption of protein, fibre, fruit and vegetables, and a high consumption of carbohydrates, sugars and fat, 22,[26][27][28][29] others did observe beneficial changes in dietary intake after BS, characterised by an increased intake of protein-rich foods and vegetables 30 and a reduced consumption of sugar-containing snacks and beverages. 30,31 However, the findings are inconsistent across different time points after surgery and most studies were limited to small sample sizes (n = 17-100).…”
Section: Introductionmentioning
confidence: 99%